If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -4x + -12 = 0 Reorder the terms: -12 + -4x + 2y = 0 Solving -12 + -4x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + -4x + 12 + 2y = 0 + 12 Reorder the terms: -12 + 12 + -4x + 2y = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -4x + 2y = 0 + 12 -4x + 2y = 0 + 12 Combine like terms: 0 + 12 = 12 -4x + 2y = 12 Add '-2y' to each side of the equation. -4x + 2y + -2y = 12 + -2y Combine like terms: 2y + -2y = 0 -4x + 0 = 12 + -2y -4x = 12 + -2y Divide each side by '-4'. x = -3 + 0.5y Simplifying x = -3 + 0.5y
| 10x+24y=123 | | 9x+11=7x+1 | | x(x-3)(x-5)=0 | | -1.9=-11.78 | | 6x-6-6=2x-4+4x | | -4.2+5x=3 | | 6n+13=67 | | n^2-2n=-1 | | 2-5=4-x | | -10t+25+3t=2t-9 | | 95-5x=13x+19 | | 2-4=4-x | | 124-5x=40x+24 | | 2x(x+21)=756 | | 10x+30=10x+30 | | 6(x-2)+5=-13 | | 3a+5=7 | | -8y-13=4y+11 | | 3(2x+18)-4x-22=7x-18 | | (2x+14)(x+14)=952 | | 5(2a-1)=9(a-5) | | -4y+4=-6y-6 | | 12x+6=54 | | 144-3x=5x-24 | | 9=5(2c-5) | | 2(x^2+14x-378)=0 | | 5x+2y=52 | | 9m+9=8m+5 | | -3=4N-(7) | | 3+3x-5=3x-2 | | 5x+3y=24 | | 5x-3y=26 |